2009
DOI: 10.1002/cvde.200806748
|View full text |Cite
|
Sign up to set email alerts
|

Initiated CVD of Poly(2‐Hydroxyethyl Methacrylate) Hydrogels: Synthesis, Characterization and In‐vitro Biocompatibility

Abstract: Initiated (i)CVD, an all-dry, one-step surface polymerization technique, was used to synthesize thin film hydrogels of poly (2-hydroxyethyl methacrylate) (PHEMA). Fourier transform infrared (FTIR) and nuclear magnetic resonance (NMR) spectroscopies showed stoichiometric PHEMA films obtained by iCVD. Differential scanning calorimetry (DSC) revealed a high glass transition temperature, indicative of high molecular mass polymer. In-vitro cell studies using adult human dermal fibroblasts (HDF) demonstrated the non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 39 publications
3
39
0
Order By: Relevance
“…Figure 2 shows the FTIR spectra of control Co-Cr (a), CC- and c). These vibrations and assignments are in agreements with those given in literatures [29,30]. The broad absorption peak at ~3400 clearly indicates the retention of the hydroxyl groups.…”
Section: 2characterization Of the Co-cr Surfaces Modificationssupporting
confidence: 88%
“…Figure 2 shows the FTIR spectra of control Co-Cr (a), CC- and c). These vibrations and assignments are in agreements with those given in literatures [29,30]. The broad absorption peak at ~3400 clearly indicates the retention of the hydroxyl groups.…”
Section: 2characterization Of the Co-cr Surfaces Modificationssupporting
confidence: 88%
“…Whereas the homopolymer piCVD pHEMA is largely linear (as compared to the PECVD PHEMA), potentially enabling lower molecular‐weight species to leach out of the pHEMA matrix over extended time in a liquid environment, the branching and random bonding introduced by PECVD hinders such mass loss, while still allowing the film to swell. Previous literature on iCVD PHEMA films show minimal monomer or oligomeric entrainment postdeposition; however, as piCVD uses a different mechanism and different temperature profile, such entrainment may have occurred in these experiments . Previously, swelling behaviors of iCVD and piCVD pHEMA were analyzed and determined to be significant for homopolymer (55 and 40% thickness increase on swelling, respectively) and iCVD pHEMA with ∼14% crosslinking (∼15% thickness increase on swelling).…”
Section: Resultsmentioning
confidence: 99%
“…Previous FTIR and NMR studies have shown PHEMA made by iCVD to be spectroscopically identical to bulk PHEMA synthesized in the liquid phase [17,18]. In our work here, FTIR shows that iCVD allows thermal decomposition of the radical initiator without harming the monomer and as a result iCVD leads to clean polymer formation that retains the chemistry of the starting monomer, including the ester and hydroxyl groups, see Figure 1.…”
Section: Discussionmentioning
confidence: 58%
“…In our work here, FTIR shows that iCVD allows thermal decomposition of the radical initiator without harming the monomer and as a result iCVD leads to clean polymer formation that retains the chemistry of the starting monomer, including the ester and hydroxyl groups, see Figure 1. In addition, by GPC, the molecular weight of PHEMA was measured to be around 2300 g/mol, and, by DSC, PHEMA was found to be a glassy polymer with a glass transition temperature between 70-90 C, depending on molecular weight [17]. PHEMA was chosen as a potential polymer electrolyte to replace the liquid electrolyte in DSSCs as its chemical functionality is expected to facilitate ion transport of the redox couple and methacrylate polymers are known to form stable gel systems with carbonate dielectrics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation